Fauna bentônica de estuários do Norte do Espírito Santo - Neves, Jacqueline de Almeida (2014)
The estuarine environment is considered one of the most important coastal ecosystems. Urban community growth mayinterferein the local environmental dynamics that suffers with strong variations of natural factors. Estuaries are home to many animal groups, including benthic invertebrates which has been used as environmental quality indicators. Thus, the aim of this study was to evaluate the composition and spatial-temporal distribution of the benthic community and relate them to environmental and anthropogenic effects observed in the estuary of the São Mateus river in Conceição da Barra municipality, alsoin the Barra Nova estuary in São Mateus municipality. The components of the benthic fauna (macro and meiofauna) behaved differently in both estuaries. In the estuary of the São Mateus river, in relation to the macrofauna, the highest values of the indices and opportunistic species abundance were found at points of higher amount of organic matter. Meiofauna and nematofauna already had significant values at the closest point to the river mouth, being influenced by salinity, hydrodynamics and sediment characteristics. As for the Barra Nova estuary, components of the fauna also behaved differently. For macrofauna,the Spiophanes gender had great abundance at the point where we registered the highest levels of organic matter, and where a terminal for transport and storage of oil is located, but no one knows for sure if that amount of organic matter is the source anthropogenic or natural, since most of the points in Barra Nova are close to the mangrove. The meiofauna and nematofauna recorded the highest abundances in point near the mouth,where it is also influenced by natural factors. On comparison between two estuaries, suggesting mostly natural factors as responsible for changes in the structure of the fauna.